ANALISIS HUBUNGAN ANTARA CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL, DAN KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2009 - 2011) - Sonni Handoko; Fuad Fuad (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to investigate the influence of corporate governance (managerial ownership, institutional ownership and proportion of board of independent commissioners) on intellectual capital (VAICTM). and the influence of the intellectual capital and corporate governance on corporate performance (ROA and M/B). In addition, this study examine whether the intellectual capital may mediate the association of corporate governance on corporate performance.The population in this study is a manufacturing company which listed on the Indonesia Stock Exchange in the year 2009-2011. 66 observed samples obtained by using purposive sampling method. The method of analysis used in this study is multiple linear regression analysis and sobel test with SPSS software.The results showed that corporate governance proxied by managerial ownership and institutional ownership doesn’t affect positively to intellectual capital, while proportion of board of independent commissioners positive influence on intellectual capital. Intellectual capital and corporate governance proxied by institutional ownership has a positive influence on corporate performance, while managerial ownership and proportion of board of independent commissioners has no effect on corporate performance. Sobel test results intellectual capital can’t mediate the association of corporate governance on corporate performance.